Once Isolated, Always Isolated?: Incidence and Characteristics of Pulmonary Vein Reconduction After Second-Generation Cryoballoon-Based Pulmonary Vein Isolation. (October 2015) - Heeger, Christian-Hendrik; Wissner, Erik; Mathew, Shibu; Deiss, Sebastian; Lemes, Christine; Rillig, Andreas; Wohlmuth, Peter; Reissmann, Bruno; Tilz, Roland Richard; Ouyang, Feifan; Kuck, Karl-Heinz; Metzner, Andreas
Abstract : Background—: The second-generation cryoballoon delivers effective pulmonary vein isolation (PVI) associated with superior 1-year clinical outcome. However, data on reconduction of previously isolated PV are sparse. Methods and Results—: A total of 421 patients underwent second-generation 28-mm cryoballoon-based PVI in 2 centers (St. George's hospital and Harburg hospital, Hamburg, Germany) between June 2012 and May 2015. Sixty-six of 421 (16%) patients (39/66, 59% women; mean age, 63±10 years, mean left atrium diameter, 45±6 mm) with a history of paroxysmal (40/66, 61%) or persistent atrial fibrillation and atrial tachyarrhythmia recurrences despite previous successful second-generation 28-mm cryoballoon-based PVI were included in this analysis. During the index PVI, the standard freeze cycle duration was 240 s. After successful PVI, a bonus freeze cycle of 240 s was applied in the first 15 of 66 (23%) patients, whereas no bonus freeze cycle was applied in the remaining patients. Repeat procedures were performed after a median of 205 (131–357) days following the index ablation. Electric reconduction was assessed for all PVs, and reablation was performed using radiofrequency energy. Persistent electric isolation was noted in 178 of 258 (69%) PVs. In 17 of 66 (26%) patients, all previously targeted PVs remained isolated. A significant difference toward highest reconduction rate for the posteroinferior segment of the right inferior PV was found ( P =0.0002). Conclusions—: The second-generation cryoballoon ablation is associated with a high rate of persistent PVI. The posteroinferior segment of the right inferior PV showed the highest reconduction rate and seems to be a predilection site for PV reconduction.